The critical roles and therapeutic implications of tuft cells in cancer - Li, Lin; Ma, Mengmeng; Duan, Ting; Sui, Xinbing (Frontiers in Pharmacology, 2022)
Tuft cells are solitary chemosensory epithelial cells with microvilli at the top, which are found in hollow organs such as the gastrointestinal tract, pancreas, and lungs. Recently, an increasing number of studies have revealed the chemotactic abilities and immune function of the tuft cells, and numerous efforts have been devoted to uncovering the role of tuft cells in tumors. Notably, accumulating evidence has shown that the specific genes (POU2F3, DCLK1) expressed in tuft cells are involved in vital processes related with carcinogenesis and cancer development. However, the interaction between the tuft cells and cancer remains to be further elucidated. Here, based on an introduction of biological functions and specific markers of the tuft cells, we have summarized the functional roles and potential therapeutic implications of tuft cells in cancers, including pancreatic cancer, lung cancer, gastric cancer, colon cancer, and liver cancer, which is in the hope of inspiring the future research in validating tuft cells as novel strategies for cancer therapies.